Short-term interactive effects of ultraviolet radiation, carbon dioxide and nutrient enrichment on phytoplankton in a shallow coastal lagoon - Domingues, Rita B. (2017)
The main goal of this study was to evaluate short-term interactions between increased CO2, UVR and inorganic macronutrients (N, P and Si) on summer phytoplankton assemblages in the Ria Formosa coastal lagoon (SW Iberia), subjected to intense anthropogenic pressures and highly vulnerable to climate change. A multifactorial experiment using 20 different nutrient-enriched microcosms exposed to different spectral and CO2 conditions was designed. Before and after a 24-h in situ incubation, phytoplankton abundance and composition were analysed. Impacts and interactive effects of high CO2, UVR and nutrients varied among different functional groups. Increased UVR had negative effects on diatoms and cyanobacteria and positive effects on cryptophytes, whereas increased CO2 inhibited cyanobacteria but increased cryptophyte growth. A positive synergistic interaction between CO2 and UVR was observed for diatoms; high CO2 counteracted the negative effects of UVR under ambient nutrient concentrations. Nutrient enrichments suppressed the negative effects of high CO2 and UVR on cyanobacteria and diatoms, respectively. Beneficial effects of CO2 were observed for diatoms and cryptophytes under combined additions of nitrate and ammonium, suggesting that growth may be limited by DIC availability when the primary limitation by nitrogen is alleviated. Beneficial effects of high CO2 and UVR in diatoms were also induced or intensified by ammonium additions.